A critical review of analytical ultracentrifugation and field flow fractionation methods for measuring protein aggregation - Liu, Jun (Springer-Verlag, 2006)
Analytical ultracentrifugation (AUC) and field flow fractionation (FFF) are 2 important biophysical methods for measuring protein aggregates. Both methods can separate protein monomer from its aggregate forms under a broad range of solution conditions. Recent advances in instrumentation and data analysis, particularly in the field of analytical ultracentrifugation technology, have significantly improved the capability and sensitivity of these biophysical methods for detecting protein aggregates. These advances have resulted in an increased use of these methods in the biopharmaceutical industry for characterization of therapeutic proteins. However, despite their many advantages over conventional methods, the difficulty in the use of the instrumentation and the complexity of data analysis process, have often hampered the widespread use and proper interpretation of data. This article reviews the recent progress in both technologies, and a few case studies are also presented to discuss their advantages and limitations.